1992
DOI: 10.21273/hortsci.27.5.436
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Selection versus Methods that Use Genotype × Environment Interaction in Sweet Corn Trials

Abstract: The analysis of variance of a data set made up of 30 sweet corn (Zea mays L.) hybrids evaluated over 5 years for marketable ears (dozens per hectare) indicated a significant genotype (hybrid) × year (GY) interaction. Three selection methods were compared: 1) a conventional method based on mean yield alone (YA), 2) Kang's ranksum (KRS) method, and 3) Kang's modified rank-sum (KMR) method. The number of hybrids selected on the basis of YA, KRS, and KMR was 13. The KRS selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Only recently has attention been focussed on usefully incorporating GE interaction into genotype selection in short-term trials . Despite availability of and comparisons among several methods designed to combine yield and stability into a single selection criterion (Kang et al, 1990;Bachireddy et al, 1992), practical integration of stability of performance with yield has not been achieved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently has attention been focussed on usefully incorporating GE interaction into genotype selection in short-term trials . Despite availability of and comparisons among several methods designed to combine yield and stability into a single selection criterion (Kang et al, 1990;Bachireddy et al, 1992), practical integration of stability of performance with yield has not been achieved.…”
mentioning
confidence: 99%
“…Understanding that the main purpose of crop performance trials is to estimate or predict, with past performance data, genotype performance in future years, especially on growers' farms, may clarify this misconception. Especially when a crossover type of GE interaction [i.e., one that causes genotype rank changes; (Baker, 1990)] is present, mean yield of genotypes selected via a method that combines yield and stability would usually be lower than that of genotypes selected on the basis of yield alone Bachireddy et al, 1992). However, the lower yield relates to past performance, and it would not necessarily translate into reduced yield on growers' farms.…”
mentioning
confidence: 99%
“…Efforts have been made to combine yield and performance stability into a single selection criterion (Kang et al ., 1991 ;Bachireddy et al ., 1992) . Benefit to farmers of emphasizing stability of performance during the selection process has been demonstrated (Kang, 1993) .…”
mentioning
confidence: 99%
“…Whereas, variance due to residual (pooled deviation) for all characters was significant except both fiber weight/plant and fruiting zone length, indicated that genotypes differed with respect to their stability suggesting that prediction would be difficult, which means that mean performance alone (mean yield) would not be appropriate. In such situation, methods that combine yield and stability of performance are useful (Bachireddy et al, 1992).…”
Section: Variabilitymentioning
confidence: 99%
“…The yield level, yield stability and genetic variance of the base populations would thus determine the success of any selection programs (Kofoid et al, 1978). Efforts have been made to combine yield and performance stability into a single selection criterion (Kang et al, 1991 andBachireddy et al, 1992). Benefit to farmers of emphasizing stability of performance during the selection process has been demonstrated (Kang, 1993 andMagari, 1995).…”
Section: Introductionmentioning
confidence: 99%